Quantum Model based on Fluid Energy Laws and String Solution for Laser Cooling Dependent on the Photon Density and Frequency - A. H, Habib.; Dirar AbdAlla, Mubarak; A. Aham, Najwa Idris; Widaa, Einas M.A.; Mohammed, Elharam A. E. (JOURNAL OF ADVANCES IN PHYSICS, 2025)
A useful expression for cooling conditions was found using energy conservation Law of a fluid for liquids and gases by treating atoms as vibrating strings subjected to gas and photon pressure. These conditions can be applied to nano and quantum systems since the model recognises the particle dual nature, which is the corner stone of quantum laws. The findings showed that the atoms density, as well as the photon density and frequency, affected the cooling process. High cooling degree requires decreasing the gas density, increasing the applied photon density, or the frequency, or both.